Augustine on the Rich Man and Lazarus (Lk 16:19-31) - Dunn, Geoffrey D. (Augustinianum, 2021)
Augustine's interpretation of the parable of the rich man and Lazarus from Lk 16 shows how much the parables of Jesus are open to a variety of interpretations and applications depending upon which part of the parable is emphasised. In Augustine's writings the second part of the parable only is commented upon (the exception being ep. 157) to illustrate points about the afterlife and the fate of the soul. However, in his homilies we find him engaging with both sections of the parable (this life and the afterlife). We can note the dexterity with which Augustine handled diverse themes in the parable by selectively emphasising either the fate of the rich man in this life or the next or the fate of Lazarus in this life or the next. From these different perspectives Augustine could deal with questions of wealth and poverty either materially or spiritually. This research supports the notion that whatever Augustine had to say about almsgiving is to be understood within a soteriological context to urge his congregation to be rich in humility and poor in pride.